A Fair Gender Interpretation of Qur'anic Verses on Workplace Ethics and Women's Dignity: Reconstructing Protective Values - Muhammad Bayu Fitriansyah; Tami Dewi Puspa Rahayu; Muhammad Fauzan Hizubullah (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to reconstruct the ethical, dignitarian, and protective values of women in the workplace through a gender-just interpretation of Qur’anic verses. Using a qualitative descriptive method with a feminist hermeneutical approach, this research analyzes texts and socio-historical contexts through library research involving primary sources (the Qur’an and classical contemporary exegeses) and secondary sources (academic papers, books, and policy documents). Findings reveal that gender-just exegesis does not alter the Qur’anic text but revitalizes its core moral message: justice (al-‘adl), human dignity (karāmah al-insān), and protection (hifz al-nafs, hifz al-‘ird, hifz al-karāmah). Three reconstructed values (professional ethics, affirmation of dignity, and women’s protection in the public sphere) redirect Qur’anic interpretation toward partnership rather than hierarchy. Theoretically, this study contributes to contemporary tafsir discourse by promoting context-aware gender justice; practically, it informs equitable and safe workplace ethics. The research concludes that Qur’anic values provide a theological and ethical foundation for women’s empowerment in modern professional spaces.